The Effect of Self Efficacy Leadership and Business Experience on Entrepreneurial Performance with Innovative Behaviour as an Intervening Variable in the Branch Management of the Indonesian Young Entrepreneurs Association in Medan City - Rojali, Ahmad; Dalimunthe, Ritha F.; Absah, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to analyze the effect of Self-efficacy, Leadership, and Business Experience on Entrepreneurial Performance with Innovative Behavior as an Intervening Variable in the Branch Management of the Indonesian Young Entrepreneurs Association of Medan City. This research uses descriptive quantitative research methods to study young entrepreneurs in the Indonesian Young Entrepreneurs Association of Medan City. This study used probability sampling and the Slovin formula to select 350 respondents. Data were collected through questionnaires and secondary sources such as literature and journals. The results showed that self-efficacy has a positive effect on entrepreneurial performance in BPC Hipmi Medan City, while leadership has a positive effect on entrepreneurial performance. Business experience also has a positive impact on entrepreneurial performance. However, self-efficacy hurts innovative behavior. This research shows that entrepreneurs in HIPMI Medan City need high self-efficacy, digital technology for innovation, and creative ideas. Leadership is essential to coordinate business goals, improve performance quality, and accept criticism to sustain the market and maintain market share.